2017
DOI: 10.7196/samj.2017.v107i10.12362
|View full text |Cite
|
Sign up to set email alerts
|

Survival of patients with Kaposi’s sarcoma in the South African antiretroviral treatment era: A retrospective cohort study

Abstract: Background When South Africa implemented its antiretroviral treatment (ART) programme in 2004, the model for treating HIV-positive Kaposi sarcoma (KS) patients shifted from symptomatic palliation to potential cure. Objective To evaluate survival and changes over time in AIDS-KS patients treated at a tertiary academic hospital oncology unit (the Steve Biko Academic Hospital (SBAH) medical oncology unit) in Pretoria in the context of ART availability in South Africa. Methods We conducted a retrospective revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 20 publications
3
33
0
Order By: Relevance
“…The proportion of T1 patients receiving chemotherapy (52.8%) and RT (25.0%) differs from treatment patterns previously reported in the same geographical area and in Gauteng Province, in that patients were more likely to receive chemotherapy than RT. [5,6] This is in keeping with international guidelines and the current protocol of the MKSC in which chemotherapy with combination bleomycin and vincristine or paclitaxel as single agent is used in all patients considered fit for chemotherapy. Radiotherapy is reserved for chemoresistant or highly localised lesions, or patients with life threatening localised lesions when chemotherapy cannot be started urgently.…”
Section: Researchmentioning
confidence: 59%
See 3 more Smart Citations
“…The proportion of T1 patients receiving chemotherapy (52.8%) and RT (25.0%) differs from treatment patterns previously reported in the same geographical area and in Gauteng Province, in that patients were more likely to receive chemotherapy than RT. [5,6] This is in keeping with international guidelines and the current protocol of the MKSC in which chemotherapy with combination bleomycin and vincristine or paclitaxel as single agent is used in all patients considered fit for chemotherapy. Radiotherapy is reserved for chemoresistant or highly localised lesions, or patients with life threatening localised lesions when chemotherapy cannot be started urgently.…”
Section: Researchmentioning
confidence: 59%
“…[15] High rates of lower limb and oral cavity involvement are in keeping with other SA cohorts. [5,6,11] The relatively low number of recorded pulmonary KS cases (11.9%) could be explained by the limited access to computed tomography scanning and the difficulty in distinguishing KS from PTB on plain chest films. Three of the 4 patients diagnosed with pulmonary KS were also on TB treatment.…”
Section: Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…study from South Africa had indicated a 2-year survival rate of less than 80% with chemotherapy or radiotherapy (4). The KS epidemic has run parallel to the HIV-1 epidemic, especially in sub-Saharan Africa where the HIV-1/AIDS epidemic continues and antiretroviral therapy (ART) has only recently become more widely available (5).…”
mentioning
confidence: 99%